New techniques for partially adaptive array design - Sng, Yeow Hong. (2009)
This thesis reports original work on several new techniques for designing partially adaptive array processors for the narrowband and the broadband environment. To cover the background of the proposed designs, a comprehensive review of the various beamforming techniques is included in the thesis. This includes generalized sidelobe canceller (GSC), multiple sidelobe canceller (MSC), beamspace approach, power minimization approach and direct nulling technique.